1980
DOI: 10.1063/1.438904
|View full text |Cite
|
Sign up to set email alerts
|

Electron photodetachment of thiomethoxyl and deuterothiomethoxyl anions: Electron affinities, vibrational frequencies, and spin–orbit splitting in CH3S⋅̄ and CD3S⋅̄

Abstract: Articles you may be interested inElectronic states and spin-orbit splitting of lanthanum dimer J. Chem. Phys. 135, 034309 (2011); 10.1063/1.3615505Laser photodetachment electron spectrometry of methoxide, deuteromethoxide, and thiomethoxide: Electron affinities and vibrational structure of CH30, CD30, and CH3SThe cross section for electron photodetachment has been measured for the thiomethoxyl anion (CH)S--) and the deuterothiomethoxyl anion (CD)S -) using an ion cyclotron resonance spectrometer in conjunction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…This value is less than 1.861 ± 0.004 eV from the photodetachment spectra experiment and a determination by the photoelectron spectrum. 22 , 23 , 36 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This value is less than 1.861 ± 0.004 eV from the photodetachment spectra experiment and a determination by the photoelectron spectrum. 22 , 23 , 36 …”
Section: Resultsmentioning
confidence: 99%
“… 21 The photodetachment experiments were also performed and yielded the C–S stretching frequency to be 680 ± 40 or 770 ± 50 in cm –1 . 22 , 23 Gillbro reported an electron spin resonance spectrum of CH 3 S produced in single crystals of CH 3 SSCH 3 from the reaction between the fluorine atom and CH 3 SH, but no definite assignment to CH 3 S was made for the observed spectra. 18 , 24 Suzuki et al.…”
Section: Introductionmentioning
confidence: 99%
“…excited state of CH 3 S − and S 2 − transitions at relative high temperature (∼600 K)[18]. The reported results from other groups also show significant discrepancy with each other and some results have relatively large errors.For the CH 3 S radical, the determined EA values are 1.8610±0.0040 eV[16,17], 1.882±0.022 eV[15], 1.871±0.012 eV[18], and 1.8670±0.0040 eV[19]. For the S 2 molecule, the determined EA values are: 1.565±0.050 eV[21], 1.663±0.040 eV…”
mentioning
confidence: 87%
“…It has been suggested that it may be an intermediate in the atmospheric oxidation by OH and NO3 (Mellouki et al, 1977) of organic sulfides such as CH3SCH3, CH3SSCH3 and CH3SH. It has been the subject of numerous spectroscopic studies, such as emission (Ohbayashi et al, 1977), the laser photodetachment (Janousek et al, 1980;Engelking et al, 1978), the electron paramagnetic resonance (EPR) (Gillbro , 1974), the IR matrix (Jacox , 1983), the laser-induced fluorescence (Chiang et al, 1991;Hsu et al, 1989;Suzuki et al, 1984) and the microwave (Endo et al, 1986).…”
Section: Introductionmentioning
confidence: 99%